Association between treatment adherence and quality of life among overweight adolescents - Pedro Miguel Lopes de Sousa; Pedro Gaspar; Helena Fonseca; Filomena Gaspar
Overweight is an extra burden for adolescent development and can trigger severe physical and psychosocial problems. This cross-sectional correlational study aimed to analyze the association between treatment adherence and obesity-related quality of life among overweight adolescents. The sample consisted of 94 adolescents attending a specialized Pediatric Obesity Clinic in Portugal, 48.94% of whom were boys and 51.06% girls, with a median age of 14.17 years (SD = 1.51). A positive correlation was found between obesity-related quality of life and adherence to weight control. The influence of parents and caregivers on the adherence to weight control is significantly associated with increased physical comfort, better social life and family relations. These results highlight the importance of behavioral change and adherence to weight control as pillars of a better quality of life among overweight adolescents. Obesity management programs need to focus on multiple criteria of treatment effectiveness, such as obesity-related quality of life.